2013
DOI: 10.1093/infdis/jit619
|View full text |Cite
|
Sign up to set email alerts
|

Complement Protective Epitopes and CD55–Microtubule Complexes Facilitate the Invasion and Intracellular Persistence of Uropathogenic Escherichia coli

Abstract: E. coli target complement-protective CD55 epitopes for invasion and exploit CD55-MT complexes to escape phagolysosomal fusion, leading to a nondestructive parasitism that allows bacteria to persist intracellularly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…6A and Fig. 6B, binding and uptake of bacteria coated bioparticles began after 10-15 min of incubation, as previously reported (Rana et al, 2014). While untreated cells exhibited a basal level phagocytosis, in cells treated with MCSF, there was a significant increase in S. aureus uptake.…”
Section: Resultssupporting
confidence: 87%
“…6A and Fig. 6B, binding and uptake of bacteria coated bioparticles began after 10-15 min of incubation, as previously reported (Rana et al, 2014). While untreated cells exhibited a basal level phagocytosis, in cells treated with MCSF, there was a significant increase in S. aureus uptake.…”
Section: Resultssupporting
confidence: 87%
“…We demonstrated a role for Afa (but not type 1 fimbriae) in the adhesion of E. coli VR50 to T24 bladder epithelial cells. Afa has been shown to mediate adherence and invasion of E. coli in HeLa and Chinese hamster ovary cells (82,83). In the case of VR50, we previously reported that the strain does not readily invade T24 cells, with low numbers observed intracellularly (84).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to adhesion, UPEC are also able to invade a number of host cell types. Once internalized in the host urothelial cells, UPEC are trafficked into late endosomal compartments forming reservoirs that allow the intracellular persistence of bacteria (Mulvey et al, 2001;Eto et al, 2006;Mysorekar & Hultgren, 2006;Rana et al, 2014).…”
Section: Discussionmentioning
confidence: 99%